Fishery culture, sustainable resources usage and transformations needed for local community development: the case of Aral Sea - Alieva, Deniza; Usmonova, Gulnoza; Shadmanov, Shukhrat; Aktamov, Sherzod (Frontiers in Marine Science, 2023)
The Aral Sea, once one of the largest lakes in the world, has been rapidly disappearing due to human activities such as irrigation and dam construction. This has had a significant impact on the fishery culture of the region, which has relied on the sea for centuries. This scientific article uses primary and secondary data to explore the history and current status of fishery culture in the Aral Sea region, the connection between the fishery culture and community. The interviews with local residents, eco-activists and students help to understand different perspectives on the matter and evaluate the challenges faced by the fishery industry due to the shrinking of the sea, including declining fish populations and changes in fishing practices. Potential solutions for sustaining fishery culture in the Aral Sea region or for transforming it in another source of income for the local community, such as promoting sustainable fishing practices, community-based tourism activities, festivals and developing alternative economic opportunities for local communities, are discussed in connection with network-based interventions. Overall, this article provides insights into how to support sustainable resource use in the region, and how the local communities are affected by disappearance of Aral Sea.